Peningkatan Aktifitas dan Hasil Belajar Siswa Melalui Penerapan Model Pembelajaran Creative Problem Solving di SMK - Riska Nurjannah; Taali Taali (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
This study aims to determine whether the Creative Problem Solving learning model can improve the competence of class XI TITL students at SMK Negeri 1 Lembah Melintang West Pasaman. This research is classroom action research. The research was carried out in each cycle of three meetings. Each cycle consists of four stages, namely planning, acting, observing, and reflecting. Data collection used the pretest, posttest instrument, last year's student score document to determine the increase in cognitive aspects, observation sheets to determine the increase in affective aspects, and student activity sheets to determine the increase in psychomotor aspects. The data analysis used is descriptive quantitative. The success criteria established for each assessment indicator reached a class average score with a minimum score of 76. The results showed that with the application of the Creative Problem Solving learning model, the competence of student groups had increased. This can be seen with an increase in the affective aspect of the first cycle, the average value of 53.46%, and an increase in the second cycle of the third meeting to 88.68%. The cognitive aspect of students has increased, seen from last year's class score of 63.83, decreasing in posttest cycle 1 to 55.1, increasing in posttest cycle II to 80.1. The average psychomotor score also increased, the psychomotor score in the first cycle of the first meeting was 81.2, increasing to 91.9 in the second cycle of meeting 3. The results of the student's learning achievement had met the minimum completeness criteria.